PENGARUH KINERJA KEUANGAN TERHADAP RETURN SAHAM SYARIAH DENGAN TINGKAT SUKU BUNGA SEBAGAI PEMODERASI - Desi Ika; Listiorini Listiorini (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2020)
The aim of this research was to analyze the relationship between return in this group stock and financial ratio. This research used MRA (Multiple Regression Analysis). Based on this research, it is concluded that partial variable of Total Asses Turnover, Current Ratio, Debt To Equity Ratio and Price Earning Ratio had no significant effect on stock return, otherwise Return On Asset variable had siginificant effect on syariah return stock in the Jakarta Islamic Index group. Simultaneously, financial performance had no significant effect on syariah return stock in Jakarta Islamic Index group. The interest rate (SBI) could not moderate the relationship between Total Asset Turnover, Current Ratio, Debt to Equity Ratio and Price Earning Ratio on stock returns, while the interest rate (SBI) could moderate (strengthen) the effect of Return On Assets on stock returns. The interest rate (SBI) is unable to moderate DER because SBI was a variable related to the company's external factors. Changes in the SBI interest rate could affect the company's financial performance because it could reduce the company's sales level so that it had an impact on the decline in company profits. The higher the SBI interest rate, the higher the return required by investors.